2009
DOI: 10.1111/j.1365-2966.2009.14678.x
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale CO survey of the Rosette Molecular Cloud: assessing the effects of O stars on surrounding molecular gas

Abstract: We present a new large-scale survey of the J = 3-2 12 CO emission covering 4.8 deg 2 around the Rosette Nebula. The results reveal the complex dynamics of the molecular gas in this region. We identify about 2000 compact gas clumps having a mass distribution given by dN/dM ∼ M −1.8 , with no dependence of the power-law index on distance from the central O stars. A detailed study of a number of the clumps in the inner region shows that most exhibit velocity gradients in the range 1-3 km s −1 pc −1 , generally di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 47 publications
6
45
0
Order By: Relevance
“…The velocity map reveals however a clear velocity difference between RN A and the large shell structure west of it. Dent et al (2009) measure a LSR velocity of 2.5 km s −1 for RN A. The shell velocity has been measured as 1.3-1.9 km s −1 in Schneps et al (1980) using CO (1-0) observations which agrees with the APEX observations.…”
Section: Globule Rn Asupporting
confidence: 69%
See 3 more Smart Citations
“…The velocity map reveals however a clear velocity difference between RN A and the large shell structure west of it. Dent et al (2009) measure a LSR velocity of 2.5 km s −1 for RN A. The shell velocity has been measured as 1.3-1.9 km s −1 in Schneps et al (1980) using CO (1-0) observations which agrees with the APEX observations.…”
Section: Globule Rn Asupporting
confidence: 69%
“…Earlier attention was drawn to this region by Wang et al (2010) who found an X-ray source at the center of the globule, and by Li (2005) who noted a highly reddened star next to the globule core. Some outflows are detected in the southern RN and the Rosette Molecular Cloud (e.g., Phelps & Ybarra 2005;Dent et al 2009) but so far only one is reported in the NW region of the RN, about 20 west of our observed field (Dent et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The northwestern (NW) part of the Rosette nebula is rich in filaments and trunks connected to the shell, which was noted early from optical images (Minkowski 1949). The shell moves away from the central OB stars at velocities of more than 20 km s −1 as concluded from surveys of associated radio molecular line emission (Schneps et al 1980;Gahm et al 2006;Dent et al 2009). Any star formed in this environment is ejected into interstellar space.…”
Section: Introductionmentioning
confidence: 98%